PENGELOMPOKKAN KABUPATEN DI PROVINSI BALI BERDASARKAN PERKEMBANGAN FASILITAS PARIWISATA - BARUS, NOVA SARI; KENCANA, I PUTU EKA NILA; SUKARSA, KOMANG GDE (E-Jurnal Matematika; Vol 2 No 3 (2013)DO - 10.24843/MTK.2013.v02.i03.p049, 2013)
The development of tourism facilities in each district/city between districts with each district is different. The purpose of this study was to determine the grouping of several districts in the province of Bali is based on the number of tourism facilities as well as what the variable identifier of each group. The analysis used in this study is the analysis of clusters and Biplot. The data used is secondary data obtained from the Bali Tourism Office in 2011. Variables used are classified hotel, non-classified hotels, home stays, restaurants, bars, tourist destination, the area of ??tourism, water tourism and business. The results of this study formed three groups: group 1 Bangli, Buleleng, Jembrana District, Klungkung, Karangasem district and Denpasar City. Group 2 and group 3 Badung district of Gianyar district. Variable identifier is a restaurant for all variables.
Keywords: Tourism facilities, Cluster Analysis, District/City in the province of Bali